Analiza porównawcza wybranych społeczeństw obywatelskich - Spustek, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article contains a comparative analysis of the civil society index of selected countries. The analysis is based on diagrams produced by CIVICUS — a supranational network of non-governmental organisations, which supports civil society actions all over the world. The author has also used the data on civil society in Poland gathered in a report by the Klon/Jawor Association. He has carried out an original analysis of the data characterising Polish civil society, using a taxonomic method and observing the criteria of four basic social dimensions: structure, environment, values and impact effects of actions.
Keywords: modelowanie; społeczenstwo obywatelskie; indeks społeczeństwa obywatelskiego